Tips and tricks in the prevention and management of vascular complications in TAVI - Antonella Tommasino; Pasqualino Sirignano; Federico Dell’Aquila; Vincenzo Fiorentini; Matteo Casenghi; Francesca Giovannelli; Stefano Rigattieri; Andrea Berni; Maurizio Taurino; Emanuele Barbato (Cirugía Cardiovascular)
Transcatheter aortic valve implantation (TAVI) has become a standard treatment for severe aortic stenosis, especially in elderly patients or those considered high-risk for surgery. Despite its increasing success, TAVI still presents challenges, particularly in the management of access site. Advances in procedure planning, device miniaturization and operator experience have mitigated these issues, but vascular complications are still common.The transfemoral approach is the most common for TAVI, although it varies widely depending on operator experience and center protocols, ranging from surgical to fully percutaneous methods. Minimally invasive techniques are increasingly favored to improve the results of the procedure. Effective management of access site complications is critical and requires careful pre-procedure planning and skilled intervention.Recent developments in ultrasound-guided access and the refinement of vascular closure devices have shown promise in reducing complications. It has also been shown that radial access as an axillary approach has a lower complication rate compared to contralateral femoral access. The integration of new devices and techniques, such as the less invasive approach, will further improve patient outcomes.This review emphasizes the importance of a comprehensive, multidisciplinary approach to TAVI and highlights the need for continued innovation and collaboration to further reduce vascular complications and improve the safety and efficacy of the procedure. As TAVI indications expand to younger populations, refinement of access management strategies and incorporation of advanced imaging and predictive tools will be critical to optimizing patient care and outcomes. Resumen: La implantación de válvula aórtica transcatéter (TAVI) se ha convertido en un tratamiento estándar para la estenosis aórtica severa, especialmente en pacientes ancianos o aquellos considerados de alto riesgo para cirugía. A pesar de su éxito creciente, el TAVI todavía presenta desafíos, particularmente en la gestión del sitio de acceso. Los avances en la planificación del procedimiento, la miniaturización de dispositivos y la experiencia del operador han mitigado estos problemas, pero las complicaciones vasculares siguen siendo comunes.El abordaje transfemoral es el más común para el TAVI, aunque varía ampliamente dependiendo de la experiencia del operador y los protocolos del centro, que van desde métodos quirúrgicos hasta completamente percutáneos. Las técnicas mínimamente invasivas son cada vez más favorecidas para mejorar los resultados del procedimiento. La gestión efectiva de las complicaciones en el sitio de acceso es crítica y requiere una cuidadosa planificación previa al procedimiento y una intervención hábil.Los desarrollos recientes en el acceso guiado por ultrasonido y el refinamiento de los dispositivos de cierre vascular han mostrado promesa en la reducción de complicaciones. También se ha demostrado que el acceso radial como un abordaje axilar tiene una tasa de complicaciones más baja en comparación con el acceso femoral contralateral. La integración de nuevos dispositivos y técnicas, como el enfoque menos invasivo, mejorará aún más los resultados de los pacientes.Esta revisión enfatiza la importancia de un enfoque integral y multidisciplinario para el TAVI y destaca la necesidad de una continua innovación y colaboración para reducir aún más las complicaciones vasculares y mejorar la seguridad y la eficacia del procedimiento. A medida que las indicaciones del TAVI se expanden a poblaciones más jóvenes, el refinamiento de las estrategias de gestión del acceso y la incorporación de herramientas avanzadas de imagen y predictivas serán críticos para optimizar el cuidado y los resultados de los pacientes.